Experimental investigations of catalytic effect of Cu2+ during anodic dissolution of iron in NaCl electrolyte. (November 2017) - Upadhyay, Ritesh Kumar; Kumar, Arbind; Srivastava, Prem Kumar
Taguchi's L9 orthogonal array has been effectively used to study the effect of process parameters such as voltage, feed rate and electrolyte concentration on material removal rate in context of two different types of electrolyte, namely, aqueous NaCl solution and CuSO4 mixed aqueous NaCl solution. The results indicated that Cu 2+ ions formed due to electrochemical reactions prevent the oxidation of Fe 2+ to Fe 3+ and catalyze the anodic dissolution of iron during machining. The experimental results were analyzed using analysis of variance method to investigate the significance and percentage contribution of individual process parameters on performance characteristics.